Norms of language choice and use in relation to listening and speaking: the realities of the practice in the Malaysian banking sector - Chan, Swee Heng; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2013)
Sociolinguists have pointed to the current linguistic development of the present era as being marked by a complex interplay of sociolinguistic concerns, among which are contradictions between global networks, local identities, (Barber, 1995; Castells, 2000), and also in norms in language choice and use. Economic and social globalization has created a strong demand for an international lingua franca, thus furthering English's presence as a global language (Crystal, 1997). However, local languages remain influential and exert a presence in a multilingual situation. This study attempts to relate the use of the global language to that of the local languages in the Malaysian banking sector which plays a dominant role as an economic powerhouse. Within this financial sector, the matrix of language as a medium of expression provides a setting for investigating situated norms of language choice and use among multilingual employees in the Malaysian banking sector. Data were collected via a survey questionnaire. Fishman's (1972) theoretical framework is adopted and extended to the workplace context in order to examine the intricacies of the norms of language choice and use in relation to specifically the listening and speaking skills. These two language skills have been prioritized by Malaysian employees as the most needed in the workplace (Abdullah et al., 2010). The study gives focus to these two skills and the specific domains of use to illustrate the competing patterns of language choice in a multilingual Malaysian workplace.